Perfection of educational-training process on the basis of account of parameters special physical preparedness of rugby-players - Pasko, V. V. (Physical Education of Students, 2014)
Purpose: to investigate the special physical fitness rugby, who were engaged in the experimental procedure. The technique is based on the application of the developed relations training load. Material : the study involved 60 athletes aged 16-18 years. Results : the program presents the main provisions of special physical preparation of athletes in the preparatory period of training macrocycle. Value for training work on special physical preparation as follows: September - the main emphasis is placed on special endurance and was 100 % of the training time; October - special endurance - 70%, strength endurance - 20% power capacity - 10%; November - respectively 50, 30, 20 %, December - 30, 40, 30 %. Conclusions : the proposed construction of a pilot version of training is more effective than traditional. It allows rational selection of training load. Also contributing to the priority development of physical qualities, gaming specialization athletes.